An Unexpected 4, 5‐Diphenyl‐2, 7‐naphthyridine Derivative with Aggregation‐Induced Emission and Mechanofluorochromic Properties Obtained from a 3, 5‐Diphenyl‐4H‐pyran Derivative. Issue 21 (28th September 2020) - Xiao, Fuming; Wang, Mengzhu; Lei, Yunxiang; Xie, Yufeng; Liu, Miaochang; Zhou, Yunbing; Gao, Wenxia; Huang, Xiaobo; Wu, Huayue
Abstract: For a specific fluorescent molecule, the increase of molecular conformation distortion is beneficial to endow it with aggregation‐induced emission (AIE) and mechanofluorochromic (MFC) properties. Herein, 3, 5‐diphenyl‐4 H ‐pyran derivative 5 and 4, 5‐diphenyl‐2, 7‐naphthidine derivative 7 with highly twisted conformations were synthesized. For compound 5, although the introduction of phenyl rings with large steric hindrance at 3 and 5 positions of the 4 H ‐pyran skeleton realized the transformation from aggregation‐induced quenching (ACQ)‐active molecule to AIE‐active molecule, it only showed a low‐contrast MFC activity. Compound 7 was accidentally obtained from compound 5 and n ‐butylamine via a ring‐opening and subsequent intramolecular ring‐closing mechanism. Compound 7 was confirmed to have a highly twisted molecular conformation by the crystal structural analysis and exhibited AIE activity originated from the restriction of intramolecular rotation. Furthermore, compound 7 exhibited reversible high‐contrast MFC activity. Upon grinding, the change of solid‐state fluorescence color from orange to yellow was confirmed to be due to the partial destruction of crystal structure. This work provides new ideas for the design and synthesis of novel AIE‐active and MFC‐active fluorescent molecules based on ACQ‐active parent molecules. Abstract : A novel 4, 5‐diphenyl‐2, 7‐naphthyridine derivative, which was accidentally obtained from a 3, 5‐diphenyl‐4 H ‐pyran derivative and n ‐butylamine via a ring‐opening and subsequent intramolecular ring‐closing mechanism, were found to exhibit aggregation‐induced emission and reversible high‐contrast mechanofluorochromic properties.